COVID-19 vaccine type-dependent differences in immunogenicity and inflammatory response: BNT162b2 and ChAdOx1 nCoV-19 - Heo, Jung Yeon; Seo, Yu Bin; Kim, Eun Jin; Lee, Jacob; Kim, Young Rong; Yoon, Jin Gu; Noh, Ji Yun; Cheong, Hee Jin; Kim, Woo Joo; Yoon, Soo-Young; Choi, Ju-Yeon; Lee, Young Jae; et al. (Frontiers in Immunology, 2022)
Evaluation of the safety and immunogenicity of new vaccine platforms is needed to increase public acceptance of coronavirus disease 2019 (COVID-19) vaccines. Here, we evaluated the association between reactogenicity and immunogenicity in healthy adults following vaccination by analyzing blood samples before and after sequential two-dose vaccinations of BNT162b2 and ChAdOx1. Outcomes included anti-S IgG antibody and neutralizing antibody responses, adverse events, and proinflammatory cytokine responses. A total of 59 and 57 participants vaccinated with BNT162b2 and ChAdOx1, respectively, were enrolled. Systemic adverse events were more common after the first ChAdOx1 dose than after the second. An opposite trend was observed in BNT162b2 recipients. Although the first ChAdOx1 dose significantly elevated the median proinflammatory cytokine levels, the second dose did not, and neither did either dose of BNT162b2. Grades of systemic adverse events in ChAdOx1 recipients were significantly associated with IL-6 and IL-1β levels. Anti-S IgG and neutralizing antibody titers resulting from the second BNT162b2 dose were significantly associated with fever. In conclusion, systemic adverse events resulting from the first ChAdOx1 dose may be associated with proinflammatory cytokine responses rather than humoral immune responses. Febrile reactions after second BNT162b2 dose were positively correlated with vaccine-induced immune responses rather than with inflammatory responses.